Theorien, Methoden und Praktiken des Interpretierens - Albrecht, Andrea; Danneberg, Lutz; Krämer, Olav; Spoerhase, Carlos (Linguae & litterae, 2015)
The interpretation of texts continues to be among the principal activities of literary scholarship. This volume compiles essays from different disciplines that reflect on the interpretation of literary texts from their different theoretical orientations, methodologies, and practices, thereby sounding out how academic research can inform literary criticism
Keywords: Konferenzschrift -- 2011 -- Freiburg im Breisgau; Interpretation; Literatur